Dose-optimised recombinant human thrombopoietin versus eltrombopag in patients with immune thrombocytopenia: a multicenter, randomised controlled trial (The TE-ITP Study)Research in context - Yunfei Chen; Ting Sun; Da Gao; Wei Wang; Zeping Zhou; Guangxun Gao; Yi Wang; Hu Zhou; Yanping Song; Yinghui Lai; Zhenyu Yan; Jinsong Yan; et al. (EClinicalMedicine)
Summary: Background: Recombinant human thrombopoietin (rhTPO) at a fixed dose of 300 U/kg/day for 2 weeks has demonstrated good efficacy and safety in adults with immune thrombocytopenia (ITP). This trial aimed to develop a flexible and personalized rhTPO regimen that ensures efficacy and safety beyond previous fixed dose, with eltrombopag as an active comparator. Methods: The TE-ITP trial was conducted in 12 centers across China. Adult ITP patients with platelet count <30 × 109/L were randomised (2:1) to receive rhTPO or eltrombopag. The initial dose in patients with baseline platelet count of 20–30 × 109/L versus <20 × 109/L was 300 versus 600 U/kg/day for rhTPO and 25 versus 50 mg/day for eltrombopag, respectively. Dosage was adjusted weekly according to platelet count, with maximum of 600 U/kg/day for rhTPO and 75 mg/day for eltrombopag. The primary endpoint was the time to first platelet count ≥50 × 109/L. The trial is registered on ClinicalTrials.gov (NCT05583838). Findings: Between November 22, 2022 and January 16, 2024, the trial enrolled 157 patients (median age: 52 years; 104 women): 105 and 52 in the rhTPO and eltrombopag groups, respectively. Baseline platelet count was <20 × 109/L in 57.1% (60/105) and 57.7% (30/52) in the rhTPO and eltrombopag groups, respectively. The median time to the first platelet count ≥50 × 109/L was 7 days (95% CI 6.0–7.0) in the rhTPO group versus 15 days (95% CI 9.0–25.0) in the eltrombopag group (p < 0.001). The risk of bleeding was lower in the rhTPO group (OR 0.523, 95% CI 0.360–0.758; p < 0.001). Adverse events occurred in 45.7% (48/105) and 60.8% (31/52) in the rhTPO and eltrombopag groups, respectively. Interpretation: The optimised rhTPO regimen, with individualized dosing based on platelet response, showed faster platelet elevation and lower bleeding risk than eltrombopag. Funding: This trial was supported by grants from the CAMS Innovation Fund for Medical Sciences (CIFMS) (2023-I2M-2-007), Noncommunicable Chronic Diseases-National Science and Technology Major Project (2023ZD0500803), National Natural Science Foundation of China (82430010), Tianjin Municipal Science and Technology Commission Grant (24ZXZSSS00230).